The Sarcomeric Protein Nebulin: Another Multifunctional Giant in Charge of Muscle Strength Optimization - Ottenheijm, Coen; Granzier, Henk; Labeit, Siegfried (Frontiers in Physiology, 2012)
The sliding filament model of the sarcomere was developed more than half a century ago. This model, consisting only of thin and thick filaments, has been successful in explaining many, but not all, features of skeletal muscle. Work during the 1980s revealed the existence of two additional filaments: the giant filamentous proteins titin and nebulin. Whereas the role of titin rapidly progressed, nebulin’s role in muscle structure and function remained long nebulous. An important feature of muscle structure and function that has remained relatively obscure concerns the mechanisms that are involved in regulating thin filament length. Filament length is an important aspect of muscle function as force production is proportional to the amount of overlap between thick and thin filaments. Recent advances, due in part to the generation of nebulin KO models, reveal that nebulin plays an important role in the regulation of thin filament length, most likely by stabilizing F-actin assemblies. Another structural feature of skeletal muscle that has been incompletely understood concerns the mechanisms involved in maintaining Z-disk structure and the regular lateral alignment of adjacent sarcomeres during contraction. Recent studies indicate that nebulin is part of a protein complex that mechanically links adjacent myofibrils. In addition to these structural roles in support of myofibrillar force generation, nebulin has been also shown to regulate directly muscle contraction at the level of individual cross bridges: cycling kinetics and the calcium sensitivity of force producing cross-bridges is enhanced in the presence of nebulin. Thus, these recent data all point to nebulin being important for muscle force optimization. Consequently, muscle weakness as the lead symptom develops in the case of patients with nemaline myopathy that have mutations in the nebulin gene. Here, we discuss these important novel insights into the role of nebulin in skeletal muscle function.